Christ in the Emotional Songs of Dr. Ali Shariati - Hussain, Yousaf (sourcecoder, 2024)
Dr. Ali Shariati, a Muslim intellectual and reformer in Iran, has expressed his gratitude and inner feelings about the Jesus. It shows the potent roots of loving Jesus in Dr. Ali Shariati’s feelings and emotions. In Ali Shariati’s blank verses, the Jesus is symbolic character of God. Repugnant to his common belief and social status among the Iranian Muslim intellectual, Shariati has shown his feelings to Jesus and it seems he was inspired of the Jesus personality and teachings. In his poems and poetic prose he believes in trinity. This article consists of those blank verses and poetic prose that Shariati has written about the Jesus Christ.